2010
DOI: 10.4322/floram.2011.007
|View full text |Cite
|
Sign up to set email alerts
|

Micobiota do solo de uma área de duna na Restinga da Marambaia, Rio de Janeiro, RJ

Abstract: RESUMOEste trabalho avaliou a micobiota do solo de uma duna nos terços inferior, médio e superior de encosta, localizada na Restinga da Marambaia, RJ. A área de estudo com aproximadamente 500 m 2 está dividida em três terços, com a vegetação variando de arbustiva a arbórea. Foi delimitada uma gleba de dimensões de 50 x 50 m, onde foram abertas cinco minitrincheiras até a profundidade de 10 cm para coleta, sendo coletadas três amostras compostas formadas a partir da reunião de cinco amostras simples para anális… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
2
1
1
Order By: Relevance
“…arenicola, P. corylophilum, P. decumbens, P. echinulatum, P. javanicum, P. miczynskii, P. paxilli, P. purpurogenum, P. sclerotiorum, and P. simplicissimum were identified. According to the authors, two species belonging to this genus could not be identified based on morphology (Fraga et al, 2010b). In the present study, in contrast to the work of Fraga et al (2010b), only Penicillium javanicum and P. paxilli were isolated from sugarcane-cultivated soils.…”
Section: Discussioncontrasting
confidence: 85%
“…arenicola, P. corylophilum, P. decumbens, P. echinulatum, P. javanicum, P. miczynskii, P. paxilli, P. purpurogenum, P. sclerotiorum, and P. simplicissimum were identified. According to the authors, two species belonging to this genus could not be identified based on morphology (Fraga et al, 2010b). In the present study, in contrast to the work of Fraga et al (2010b), only Penicillium javanicum and P. paxilli were isolated from sugarcane-cultivated soils.…”
Section: Discussioncontrasting
confidence: 85%
“…The soil belongs to the Quartzipsamment order (Menezes et al, 2005). Soil fertility increases in the upper third of the dune, in comparison to the lower third, which presents the highest aluminum content and lowest nutrient content (Fraga et al, 2010). Regarding the topsoil chemical attributes (0-0.10 cm) in the upper third of the dune, Fraga et al (2010) obtained the following results: K + : 29.67 mg kg -1 ; Ca 2+ : 3.27 cmol c kg -1 ; Mg 2+ : 1.62 cmol c kg -1 ; Na + : 0.14 cmol c kg -1 .…”
Section: Methodsmentioning
confidence: 97%
“…This forest grows on the top of a single dune with about 30 m height, covering about 527 ha and corresponding to approximately 10.7% of the total area of Restinga da Marambaia. The vegetation profile in the dune varies from shrub, located in the lower third, to an arboreal community which predominates in the upper third (Fraga et al, 2010 (11.27) and Pseudopiptadenia contorta (10.13).…”
Section: Methodsmentioning
confidence: 99%
“…No Brasil, são encontrados poucos estudos direcionados para espécies de Trichocomaceae em ambientes de florestas tropicais. Os relatos são citações de algumas espécies em diferentes estudos, como: ' A Ocorrência de Aspergillus e Penicillium em solo na região norte (Pará e Maranhão)' , por Batista et al (1967a, b), 'Solo de Duna no Rio de Janeiro (Fraga et al, 2010b)' e ' Ambiente de Florestamento de Pinus e Corymbia' (Fraga et al, 2010a …”
Section: áRea Menos Impactadaunclassified